Microbial diversity patterns in the root zone of two Meconopsis plants on the Qinghai-Tibet Plateau - Chen, Shuting; Cao, Pengxi; Li, Ting; Wang, Yuyan; Liu, Xing (PeerJ, 2023)
In the extreme alpine climate of the Qinghai-Tibet Plateau (QTP), plant growth and reproduction are limited by extremely cold temperatures, low soil moisture, and scarce nutrient availability. The root-associated microbiome indirectly promotes plant growth and plays a role in the fitness of plants on the QTP, particularly in Tibetan medicinal plants. Despite the importance of the root-associated microbiome, little is known about the root zone. This study used high-throughput sequencing to investigate two medicinal Meconopsis plants, M. horridula and M. integrifolia, to determine whether habitat or plant identity had a more significant impact on the microbial composition of the roots. The fungal sequences were obtained using ITS-1 and ITS-2, and bacterial sequences were obtained using 16S rRNA. Different microbial patterns were observed in the microbial compositions of fungi and bacteria in the root zones of two Meconopsis plants. In contrast to bacteria, which were not significantly impacted by plant identity or habitat, the fungi in the root zone were significantly impacted by plant identity, but not habitat. In addition, the synergistic effect was more significant than the antagonistic effect in the correlation between fungi and bacteria in the root zone soil. The fungal structure was influenced by total nitrogen and pH, whereas the structure of bacterial communities was influenced by soil moisture and organic matter. Plant identity had a greater influence on fungal structure than habitat in two Meconopsis plants. The dissimilarity of fungal communities suggests that more attention should be paid to fungi-plant interactions.
Keywords: Microbial community; Bacterial communities; Fungal communities; Soil properties; Community ecology; Microbial structure